A case of cardiac sarcoidosis presenting with double tachycardia. Issue 1 (27th June 2014) - Takahashi, Keiko; Okumura, Yasuo; Watanabe, Ichiro; Nagashima, Koichi; Mano, Hiroaki; Sonoda, Kazumasa; Kogawa, Rikitake; Sasaki, Naoko; Iso, Kazuki; Okubo, Kimie; Nakai, Toshiko; Hirayama, Atsushi
Abstract: Although the most feared cardiac manifestation in cardiac sarcoidosis is the onset of ventricular arrhythmia, some patients may present with supraventricular arrhythmias. We present a rare case of cardiac sarcoidosis associated with double tachycardia manifesting as atrial flutter and ventricular tachycardia.